2019
DOI: 10.1016/j.ympev.2019.106523
|View full text |Cite
|
Sign up to set email alerts
|

Morphological species and discordant mtDNA: A genomic analysis of Phrynocephalus lizard lineages on the Qinghai-Tibetan Plateau

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…The RADseq methodology has been applied in other studies of squamate (lizards and snakes), increasing understanding of the processes related to genetic divergence and the identification of genomic regions of interest. The total number of SNPs obtained in this study (288,286) agree with the SNP density found in other RADseq studies of reptiles, with relatively high levels of diversity detected 30,31 . Population structure analysis revealed a clear genetic structure among all the populations of P. lilfordi, independent of whether we used SNPs from all RAD tags or just candidates for selection 32 .…”
Section: Discussionsupporting
confidence: 90%
“…The RADseq methodology has been applied in other studies of squamate (lizards and snakes), increasing understanding of the processes related to genetic divergence and the identification of genomic regions of interest. The total number of SNPs obtained in this study (288,286) agree with the SNP density found in other RADseq studies of reptiles, with relatively high levels of diversity detected 30,31 . Population structure analysis revealed a clear genetic structure among all the populations of P. lilfordi, independent of whether we used SNPs from all RAD tags or just candidates for selection 32 .…”
Section: Discussionsupporting
confidence: 90%
“…Jin and Brown [86] demonstrated that morphologically different P. guinanensis is genetically indistinguishable from P. putjatai (spelled as "P. putjatia" in their work; however "P. putjatai" is the correct spelling according to Barabanov and Ananjeva [1]). Our study agrees with the results of Jin and Brown [86,122] and Jin et al [123] on the phylogenetic position of P. guinanensis (Figure 2B). The recent multilocus phylogenetic study by Chen et al [121] reported on three major lineages within P. putjatai.…”
Section: Oreosaura (Phrynocephalus Vlangalii Species Group)supporting
confidence: 93%
“…Interspecific gene flow can blur the morphological boundary of species because the morphology of hybrid offspring will show a parental intermediate type, resulting in errors of individual identification in a discriminant analysis (Jones et al, 2016;Flores-Rentería et al, 2017). In particular, it is difficult to classify and define species complexes with similar morphology and incomplete reproductive isolation, because interspecific hybridization can cause inconsistency between taxonomic status and phylogenetic relationships (Chan et al, 2017;Jin and Brown, 2019). In addition, due to rapid changes in the geological structure and climatic fluctuation in the middle and late Pleistocene, the rate of genetic differentiation was accelerated in O. graminea sensu stricto, and three clades evolved within a short period (2.19 MYA) (Chen et al, 2020).…”
Section: Incomplete Morphological Differentiationmentioning
confidence: 99%